New public service improvement in the border area. Case Study in Entikong District, Sanggau City, Indonesia - Rusdiono; Anwar, Hairil; Sihaloho, Nahot Tua Parlindungan (Technium Social Sciences Journal, 2022)
Public services in Entikong District have been strengthened by the Citizen’s Charter, including the PATEN standard, the sub-district public service process flow, the vision and mission of services and service promises, and the central values contained in the core values and employer branding. Come, we are ready to serve cheerfully "fast, effective and efficient, friendly, sincere and trustworthy." The method used in this research is a descriptive method with a qualitative approach. The method of data collection was carried out by in-depth interviews with the ranks of the sub-districts who were directly involved in administrative services and community and community leaders. After the data is collected, the next step is a verification and further analysis based on the theory used as a reference to produce conclusions. The research objective is to explain the quality of public services in the Entikong sub-district, which while the theory has not explained it, by identifying and providing a more logical and actual explanation and finding and recommending the Development of new patterns or models of public services, as well as gaining new knowledge, understanding and concepts in a comprehensive study, especially in the study of public services in the field of public administration. Based on the results and discussion of the research, then a new public service development model was created to improve the quality of public services in the Entikong sub-district, and its strengthening and a new concept were built that was useful in enriching the existing new public service concept. The new concept proposed by the researcher is: "Development of new public services with values; desire to serve, democracy in service, the spirit of public administration, Citizen’s first and service principles can be developed in improving the quality of public services if the elements of the Citizen’s Charter include service standards, service flow, service vision and mission, and service promises, as well as core values and employer branding as the central values accepted by all staff, has been well internalized by public service providers.